2022
DOI: 10.1002/pc.26807
|View full text |Cite
|
Sign up to set email alerts
|

Performance of polylactic acid/polycaprolactone/microcrystalline cellulose biocomposites with different filler contents and maleic anhydride compatibilization

Abstract: In this study, polylactic acid (PLA)/polycaprolactone (PCL)/microcrystalline cellulose (MCC) composites and PLA/PCL/MCC composite compatibilized by the maleic anhydride (MA) copolymer were prepared via two‐screw extrusion technology. The mechanical results showed that the strength and break elongation of the ternary composites are decreased with the increase in the MCC contents. After the grafting copolymer was added, due to the better compatibility between the components of the composite, the strength and bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…41 This signal indicated that MA monomers were grafted onto the PLA backbone when MA was transformed to a saturated anhydride, with the occurrence of succinic anhydride end-grafting, which is a desirable structure of grafted polymers. 42 The absence of a band at 1590 cm −1 , related to cyclic C = C stretching of MA, 43 indicated that MA was grafted onto PLA. The characteristic peak of anhydride at 1750 cm −1 could not be easily identified, due to overlap with the intense peak for C = O in PLA.…”
Section: Resultsmentioning
confidence: 99%
“…41 This signal indicated that MA monomers were grafted onto the PLA backbone when MA was transformed to a saturated anhydride, with the occurrence of succinic anhydride end-grafting, which is a desirable structure of grafted polymers. 42 The absence of a band at 1590 cm −1 , related to cyclic C = C stretching of MA, 43 indicated that MA was grafted onto PLA. The characteristic peak of anhydride at 1750 cm −1 could not be easily identified, due to overlap with the intense peak for C = O in PLA.…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR of PLA and PLA-g-GMA spectra are presented in Figure 4A. The asymmetric vibration peak of epoxy group of GMA appeared in PLA-g-GMA 13 C NMR and (B) 1 H NMR spectra of PLA and PLA-g-GMA.…”
Section: Compatibilizer Analysismentioning
confidence: 99%
“…Polylactic acid (PLA) served as the most promising biodegradable polymer has high strength, great biocompatibility, and excellent processing property. [ 1 ] In addition, there is a variety of raw materials for synthesizing PLA, including wheat, corn, and potato. However, due to the specialty of the molecular structure, PLA has significant drawbacks that restrict the range of applications, including high brittleness and low crystallinity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, Ye et al called attention to the PCL/ PLA/ microcrystalline cellulose composites fabricated via extrusion technology. The innovative development exhibited high biocompatibility and adhesion of human breast cancer cells, indicating a bright future in bioengineering research [ 208 ].…”
Section: Introductionmentioning
confidence: 99%